Medical decision-making inspired from aerospace multisensor data fusion concepts. (September 2015) - Pombo, Nuno; Bousson, Kouamana; Araújo, Pedro; Viana, Joaquim
<x xml:space="preserve">Abstract</x> In recent years, Internet-delivered treatments have been largely used for pain monitoring, offering healthcare professionals and patients the ability to interact anywhere and at any time. Electronic diaries have been increasingly adopted as the preferred methodology to collect data related to pain intensity and symptoms, replacing traditional pen-and-paper diaries. This article presents a multisensor data fusion methodology based on the capabilities provided by aerospace systems to evaluate the effects of electronic and pen-and-paper diaries on pain. We examined English-language studies of randomized controlled trials that use computerized systems and the Internet to collect data about chronic pain complaints. These studies were obtained from three data sources: BioMed Central, PubMed Central and ScienceDirect from the year 2000 until 30 June 2012. Based on comparisons of the reported pain intensity collected during pre- and post-treatment in both the control and intervention groups, the proposed multisensor data fusion model revealed that the benefits of technology and pen-and-paper are qualitatively equivalent <![CDATA[ opagenumbers (50, 68 [ 53, 2 ± 3, 59 ] and 53, 2 [ 50, 68 ± 3, 72 ]) ]]> . We conclude that the proposed model is suitable, intelligible, easy to implement, time efficient and resource efficient.